Legal Study on Criminal Sanctions in Certain Airport Area (Mimbar Keadilan, 2023)
The purpose of this study is to examine criminal sanctions in certain areas at the airport. An airport is a facility where aircraft can take off and land. The importance of aviation safety and security is the responsibility of the Airport Authority. Therefore, it is necessary to limit the area or security area, because an airport is a place that is prone to crime, so there are criminal sanctions for those who break the law. Airport supervision and authority are regulated by the Airport Authority, and the government can easily monitor airport activities under the management of PT. Angkasa Pura I and PT. Angkasa Pura II. The type of research used is legal research with normative juridical methods, which analyzes using statutory and conceptual approaches. The main role of the airport authority is as a regulator of safety, and security and facilitating flight services. With the important role of the Airport Authority, there are restrictions on areas that passengers and non-passengers may pass while in the airport area. If there is an unlawful act, a criminal sanction will be imposed based on the current law. Criminal sanctions for perpetrators of crimes in the aviation industry are in the form of imprisonment and administrative fines. Criminal imposition of perpetrators of aviation crimes is a logical juridical consequence of the implementation of these statutory provisions.